1999
DOI: 10.1093/emboj/18.16.4424
|View full text |Cite
|
Sign up to set email alerts
|

Increased apoptosis induction by 121F mutant p53

Abstract: p53 mutants in tumours have a reduced affinity for DNA and a reduced ability to induce apoptosis. We describe a mutant with the opposite phenotype, an increased affinity for some p53-binding sites and an increased ability to induce apoptosis. The apoptotic function requires transcription activation by p53. The mutant has an altered sequence specificity and selectively fails to activate MDM2 transcription. Loss of MDM2 feedback results in overexpression of the mutant, but the mutant kills better than wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 83 publications
(107 reference statements)
5
103
0
Order By: Relevance
“…Figure 2B shows that the parental HCT116 cells were efficiently sensitized by the TAT-RasGAP 317-326 peptide to cisplatin-induced death but that the variant lacking p53 remained unaffected by the peptide. To confirm these results, we used the H1299 lung carcinoma cell line in which p53 can be repressed by tetracycline (20). As shown in Fig.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Figure 2B shows that the parental HCT116 cells were efficiently sensitized by the TAT-RasGAP 317-326 peptide to cisplatin-induced death but that the variant lacking p53 remained unaffected by the peptide. To confirm these results, we used the H1299 lung carcinoma cell line in which p53 can be repressed by tetracycline (20). As shown in Fig.…”
Section: Introductionmentioning
confidence: 80%
“…We next used p53 proteins bearing various alanine substitutions at sites known to be phosphorylated following DNA damage (27), including some (e.g., Ser 15 and Ser 20 ) that have been shown in vivo to play important role in p53-induced apoptosis and tumor suppression (28). Cells expressing p53 mutants with one or two of these point mutations (at position 33-37, 15, and 20) were less sensitive to cisplatin than wildtype p53-expressing cells (Fig.…”
Section: Tat-rasgap 317-326 -Induced Sensitization Of Tumor Cells Reqmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with those from previously published microarray studies. 11,24,25 Saller et al first identified CYFIP2 (also known as PIR121) as a candidate p53 target gene whose mRNA was up regulated 5.3X by wild-type p53, 15.3X by a pro-apoptotic p53-121F mutant, and not induced in response to an anti-apoptotic p53-277R mutant, respectively, when stably expressed under TET control in H1299 cells or adenovirally expressed in Saos-2 (null for p53) or U2OS (expressing WT p53) cells. Using the nucleotide analog 5-fluorouracil, a DNA damage inducing chemotherapeutic drug, Kho et al detected a 2X increase in CYFIP2 mRNA by microarray in HCT116 cells in a p53-dependent manner, suggesting that CYFIP2 can be induced by endogenous p53.…”
Section: Discussionmentioning
confidence: 99%
“…5 The retrieved cDNA band from DD was subcloned into the pCR-TRAP vector and utilized for sequencing and Northern blotting as previously described. 5 The pRD1-215 plasmid, obtained from R. Iggo, 11 containing the full-length CYFIP2/PIR121 cDNA was used as a probe for the CYFIP2 Northern blot.…”
Section: Methodsmentioning
confidence: 99%